(untitled) (Ustozlar uchun, 2026)
This article examines the anthropocentric approach to cultural transfer in translation, emphasizing the central role of the translator as an active agent in meaning construction. It analyzes how culture-specific elements such as idioms, traditions, and realia are conveyed from the source language into the target language through the prism of human cognition and cultural competence. Special attention is given to the translator’s individual decisions, background knowledge, and interpretative strategies, which significantly affect the translation outcome. The study also explores major translation strategies, including domestication, foreignization, and adaptation, in the process of cultural transfer. Furthermore, it discusses the challenges related to translating culture-bound items and highlights the importance of balancing fidelity to the source text with clarity for the target audience. The findings indicate that the anthropocentric approach enhances translation quality by prioritizing human and cultural factors.